Irradiative thermoluminescence, and defect center analysis in Ni2+ ionic CaAl2SiO6 glass lattice. (November 2022) - Veerabhadra Rao, K.; Ramesh, Ch; Devi, S. Shashi; Ashok, Padala; Guntu, Ravi Kumar; Bhikshamaiah, G.; Appa Rao, B.
Abstract: In this study, we obtained nickel oxide-doped CaAl2 SiO6 glasses and analyzed their structural, optical, thermoluminescent, and photoluminescent properties. In general, NiO-doped glasses are useful as optical materials. However, optical materials such as glasses containing Ni 2+ ions require refinement of their properties in terms of their structure, thermal stability, microhardness, electrical conductivity, and luminescence to facilitate the development of advanced thermoluminescent materials. Thus, Ni 2+ ionic CaAl2 SiO6 glasses were synthesized and tested in this study. We observed the amorphous behavior of samples by X-ray diffraction, scanning electron microscopy, differential thermal analysis, and Fourier transform-infrared (FT-IR) spectroscopy. The order of density, oxygen packing density, polaronic radius, molar volume, and refractive index were evaluated for the glasses. The glass transition temperatures were identified using DTA to assess the order of the thermal stabilities, where the highest was found for the Ni0.6 Ca9.4 Al30 Si60 glass. The modes of molecular vibrations for Ni–O–Ni, Ca–O–Ca, Al–O–Al, and Si–O–Si molecules were identified using FT-IR. The highest transmittance intensities were determined for the Ni0.6 Ca9.4 Al30 Si60 glass. The order of the electrical conductivity and activation energy were obtained for glasses using DC conductivity measurements, where the highest was found for the Ni0.6 Ca9.4 Al30 Si60 glass. Optical absorption spectra were recorded for the glasses to determine the order of the band gap (∼0.78 eV) and nephelauxetic ratio (0.799). The photoluminescence was recorded for the glasses at an excitation wavelength of 400 nm to determine the order of the transition probability (∼1.85 S –1 ) and luminescence emission cross section (∼0.819 × 10 −34  cm 2 ). The highest transmittance intensities were obtained for the Ni0.6 Ca9.4 Al30 Si60 glass. Thermoluminescence was recorded for the glasses under gamma irradiation at a dose of 30 kGy, which yielded the shape symmetry factor (∼0.535%), frequency factor (1.31 S –1 ), and activation energy (∼0.551 eV). Irradiative thermoluminescent analysis suggested a higher order octahedral tendency, and the divalent oxidation states for nickel ions in the glass with an NiO concentration of 0.6 mol% obtained the best thermoluminescent intensities. The orders of the elastic modulus, nephelauxetic ratio, and microhardness for the glasses suggested covalently connected elastic lattices. Highlights: Microhardness range of the glasses, reveal the elastic strength. Which is found to be high in comparison with borophosphate glasses. The d. c. Conductivity range of glasses suggest higher orders of polaronic radius, interstitial defects, and the octahedral tendency of Ni 2+ ions, with in the glasses. The order of ionic radius, trap centers, and the octahedral tendency of Ni 2+ ions, with in the glasses suggest glasses will be useful advanced TL resource. The shape symmetry factor and low A.E.'s of the glasses under thermoluminescence studies suggest materials are TL active for low energies. The order of the optical bandgap, transition probability and cross-section of the glasses are a highly suggestible for photonic resource. Due to the high orders of refractive index, the octahedral tendency of Ni 2+ ions, and nephelauxetic ratio, the Ni-0.6 glass exhibited best spectroscopic properties in comparison.